If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 14 + 15x Solving 7x = 14 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 7x + -15x = 14 + 15x + -15x Combine like terms: 7x + -15x = -8x -8x = 14 + 15x + -15x Combine like terms: 15x + -15x = 0 -8x = 14 + 0 -8x = 14 Divide each side by '-8'. x = -1.75 Simplifying x = -1.75
| 4(y+4)=5(y-3) | | 6.7+12m-9.3=6.2 | | 91-3x= | | 2x*4=8 | | 2x^2+2y^2-xy+15x+30=0 | | x-15=-28 | | x^3-6x-16=0 | | (4x+3)(2x-4)= | | p^2-7p=28 | | (4x-1)/6+(2x+1)/2=2 | | 10x-9-9=14x-9+6x | | 15n+15+4n=130 | | x^2+7c+10=0 | | x+12=21 | | 4k^2-125=5k | | 7-k=5+3k | | x^2-8x*7=0 | | (x-y)(x^2+y^2)= | | -5t-14=2n | | ln(2x-3)=0 | | 2p^2-63=11p | | -2x-5-4=2x+12-x | | 5-9x=9x+21 | | 14m=-13 | | 1.666666667(3q+6)=8 | | (3x^4-5x^2-4)(-3x^3)= | | 6(2n-5)=-3(7-3n)+2n | | 276-4x=41x+16 | | 4(m+8)-12=4(m+5) | | 2.7-15p=30p-1.8 | | 18=0.5p+15 | | =-6x^2-23x-20 |